Optogenetic Gene Therapy for the Degenerate Retina: Recent Advances - McClements, Michelle E.; Staurenghi, Federica; MacLaren, Robert E.; Cehajic-Kapetanovic, Jasmina (Frontiers in Neuroscience, 2020)
The degeneration of light-detecting rod and cone photoreceptors in the human retina leads to severe visual impairment and ultimately legal blindness in millions of people worldwide. Multiple therapeutic options at different stages of degeneration are being explored but the majority of ongoing clinical trials involve adeno-associated viral (AAV) vector-based gene supplementation strategies for select forms of inherited retinal disease. Over 300 genes are associated with inherited retinal degenerations and only a small proportion of these will be suitable for gene replacement therapy. However, whilst the origins of disease may vary, there are considerable similarities in the physiological changes that occur in the retina. When early therapeutic intervention is not possible and patients suffer loss of photoreceptor cells but maintain remaining layers of cells in the neural retina, there is an opportunity for a universal gene therapy approach that can be applied regardless of the genetic origin of disease. Optogenetic therapy offers such a strategy by aiming to restore vision though the provision of light-sensitive molecules to surviving cell types of the retina that enable light perception through the residual neurons. Here we review the recent progress in attempts to restore visual function to the degenerate retina using optogenetic therapy. We focus on multiple pre-clinical models used in optogenetic strategies, discuss their strengths and limitations, and highlight considerations including vector and transgene designs that have advanced the field into two ongoing clinical trials.